Algorithm of estimation suspended sediments concentration in Bili-Bili Reservoir. Issue 3 (July 2021) - Faridah, Sitti Nur; Achmad, Mahmud; Samsuar,; Tantu, Fatimah R.
Abstract: The Bili-Bili Reservoir is located in the middle of the Jeneberang watershed in South Sulawesi Province, which was built for flood control, irrigation, raw water supply, and hydroelectric power plants. However, in the latest development, there has been a decline in utilization of the reservoir service function due to changes in the catchment area condition because of sediment. Estimation of sediment concentration in the Bili-bili reservoir was analyzed using spectrometer data. Estimation of Total Suspended Sediment (TSS) using a spectrometer by reflectance testing of the ratio between bands with various regression equations. Algorithm estimation of TSS concentration based on spectrometer measurements provides a coefficient of determination (R 2 ) of 0.800 and an RMS error of 0.088, with a 3rd order polynomial equation for the green/red bands ratio: y = 62.667x 3 – 154.328x 2 + 121.27x – 29.902.